Sentinel lymph node biopsy for oral tongue squamous cell carcinoma cT1–2N0: prospective single-center study - M. A. Kotov; Z. A.‑G. Radzhabova; S. N. Novikov; P. I. Krzhivitsky; O. I. Ponomareva; E. V. Kostromina; V. А. Kushnarev; M. A. Radzhabova (Опухоли головы и шеи, 2020)
The study objective is to evaluate the informativeness of the biopsy technique of the signal lymph node (LN) in squamous cell carcinoma of the tongue cT1–2N0.Materials and methods. A prospective, single-center study included 26 patients with morphologically verified squamous cell carcinoma of the tongue cT1–2 and the lack of clinical and radiological data for metastatic damage to the LNs of the neck. All patients underwent a radioisotope study of the lymphatic flow from the primary tumor and the topography of the signal LNs. The informativeness of the biopsy of the signal LNs was evaluated in accordance with 2 diagnostic models. When using the first diagnostic model, all LNs accumulating colloids labeled with the 99mTc isotope were considered signal LNs. In the second model, only nodes accumulating radiocolloids and located in the immediate vicinity of the primary tumor of the tongue and / or connected with the primary tumor by the “pathway” of the lymphatic vessels were considered as signal LNs. Results. The sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy, according to the 1st diagnostic model, were 66.6 % (95 % confidence interval (CI) 9.43–99.16), 100 % (95 % CI 85.18–100 %), 100 %, 95.83 % (95 % CI 82.28–99.13 %), 96.15 % (95 % CI 80.36–99.90 %), and when all LNs located along with the signal LNs were removed at the same levels as regional LNs, the sensitivity increased to 100 %. In the second model, the diagnostic values were: 33.3 % (95 % CI 0.84–90.57), 100 % (95 % CI 85.18– 100.00), 100 %, 92 % (95 % CI 83.78–96.24), 92.31 % (95 % CI 74.87–99.05 %). Conclusion. Evaluation of lymphatic outflow from the primary tumor and assessment of sentinel lymph node location in patients with stage cT1–2N0M0 squamous cell carcinoma of the tongue allow a doctor to determine the volume of lymph node dissection for each patient individually. Unilateral lymph node dissection is acceptable in patients with unilateral lymphatic outflow, whereas in patients with bilateral lymphatic outflow, it is associated with a quite high (up to 10 %) risk of metastatic lesions in the lymph nodes on the opposite side of the neck. It is necessary to excise all lymph nodes accumulating radiocontrast agent and regional lymph nodes located at the same levels.